Behavioral analysis of rapid weight reduction strategies of judo fighters in period of competition (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
In judo, athletes loose weight to compete in a below its standard weight category. The aim of this study was to investigate the strategies used by judo athletes to reduce weight. Participated in the survey nine federated judo athletes of both genders and different competitive categories with ages between 14 and 22 years. All participants were above the weights of their categories a month before the competition. Besides being subjected to weight one month and 24 hours before the competition, participants answered two questionnaires. The first (pre-competition) aimed to characterize the participants and the daily routine and training and the second (post-competition) with questions that pertain to the methods used by the participants and the results obtained relating to weight loss. Rapid weight loss strategies of the participants are analyzed in terms of intermittent reinforcement and impulsivity. Strategies and techniques based on behavior analysis principles are proposed in order to promote self-controlled behavior.
Keywords: Sport Psychology; Feeding behavior; Self-control